Edukasi Upaya Penangulangan Lahan Kritis Melalui Perluasan Wilayah Penghijauan di Desa Semangki Kabupaten Maros - Ervi Novitasari; Khaidir Rahman; Jamaluddin; Nunik Lestari; Reski Praja Putra; Amiruddin Hambali; Ilham (TEKNOVOKASI : Jurnal Pengabdian Masyarakat, 2023)
The problem faced by the people of Semangki Village is that crop productivity is decreasing as a result of unnatural use of natural resources which is not supported by the expansion of reforestation, resulting in unproductive land conditions or critical land. The expansion of reforestation is not optimal due to lack of information and knowledge of the community in making efforts to minimize critical land. Through this activity, the public can obtain the widest possible information. The method used in carrying out this activity uses the lecture and question and answer method. The results of this activity showed the high enthusiasm of the community and increased knowledge after obtaining information on educational activities. The increase that occurred from the initial ability analysis data was obtained by 25% and the final ability was 85%.